From 'the people' to the crowd: The push for independence in Catalonia. (September 2021) - Bielsa, Esperança
This article examines the sociological value of Elias Canetti's work on crowds and power. It explores crowd action and imagery in the push for Catalan independence through the analysis of materials published on Twitter by Tsunami Democràtic, which emerged to coordinate the response to the sentencing of Catalan political leaders after the unilateral declaration of independence. It then goes on to discuss how a crowd-based approach offers a supplementary perspective to contemporary studies of populism, on the one hand, and to accounts that primarily focus on the role of social media in organizing political protest movements, on the other. An analysis of crowds not only avoids both methodological holism and methodological individualism. It also helps to understand why so many people were mobilized beyond the power of concepts, ideologies and discourse.